Management Practices and Productivity Level of Cebu City and Ozamiz City Eateries during COVID-19 Pandemic - Yvette Villarta; Flordeliza Gagani; Mary Angela Dinulos; Liz Alexandra Tan; Adair Shemie Margaret Yosores; Allyza Punsalan; Andre Murillo (Journal La Bisecoman, 2022)
The COVID-19 pandemic has made drastic changes in every country’s economy, affecting several businesses particularly in the restaurant industry and resulting in different obstacles that threaten the overall business productivity. Thus, the study is a quantitative non-experimental that aimed to determine if there is a significant relationship between the management practices and productivity among the 50 respondents from the randomly selected 10 eateries in Cebu City, Philippines through linear correlation analysis. Data were gathered online using an adapted and reliable questionnaire. Findings revealed that the management practices of the eateries have a very high average weighted mean and SD (x̄=3.34 SD=0.72). Meanwhile, the level of impact of the eateries’ overall productivity garnered a very high average weighted mean (x̄=3.50 SD=0.57). Therefore, the levels of management practices and the productivity of the eateries during the COVID-19 pandemic have significant relationship with a moderate positive correlation of 0.58 (r = 0.5846, = 0.00001, p < 0.05). This implies the great need for businesses to establish appropriate management practices and for employees to systematically apply these practices for the betterment of both the productivity of the employees and the business as a whole. Additionally, with the problems of operations, regulations imposed by the government, and adjustments to competitors being faced, respondents suggested fostering open communication and utilizing online platforms, and promotions for the improvement of management practices and productivity.